Design Of Web Based RT Citizen Cover Letter System - Pramuditya, Reza Santika; Sanjaya, Ridwan; Nugroho, Agus Cahyo (Journal of Business and Technology, 2024)
The coronavirus (covid-19) pandemic has claimed many lives and poses a threat to the entire world. The government has implemented numbers of rules to suppress the spread of the coronavirus, one of them are implementing all physical activities into online. To support these rules, both the government and the community really need support from digital technologies. However, not all digital technology support is available to all citizens, like the smallest government auxiliary institutions, namely the scope of RT and RW, need digital technology assistance to provide maximum service to the community. This research aims to assist one particular service of RT and RW for the community to be maximized, which is the creation of a web-based community cover letter system.